2017
DOI: 10.4322/2526-8910.ctoar2063
|View full text |Cite
|
Sign up to set email alerts
|

Successful return to work of individuals with chronic pain according to health care providers: a meta-synthesis

Abstract: Abstract:Introduction: Chronic pain is a persistent disease that causes personal and social economic problems when individuals are unable to return to work. Objective: This meta-synthesis investigated the perspectives of health professionals on the best mechanisms (triggering change) and approaches to support people with chronic pain on return to work. Method: Peer-reviewed articles published until October 2017 were searched in databases such as PsycINFO, EMBASE, CINAHL and Pubmed. The search was based on thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In our study, the lack of collaboration between the persons with CMSP and different stakeholders and among stakeholders negatively influenced the process. Furthermore, communication and transfer of information/knowledge between stakeholders were emphasized as improving the process and would be valuable for creating standards of practice to improve the process of RTW, which are findings also confirmed by Magalhães [ 7 ]. Collaboration between different actors must consider complex relationships and social hierarchies when trying to improve these inter-professional relationships.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In our study, the lack of collaboration between the persons with CMSP and different stakeholders and among stakeholders negatively influenced the process. Furthermore, communication and transfer of information/knowledge between stakeholders were emphasized as improving the process and would be valuable for creating standards of practice to improve the process of RTW, which are findings also confirmed by Magalhães [ 7 ]. Collaboration between different actors must consider complex relationships and social hierarchies when trying to improve these inter-professional relationships.…”
Section: Discussionsupporting
confidence: 62%
“…Franche et al [ 10 ] reported strong evidence that contact between health care providers and the workplace significantly reduces the duration of work disability. Furthermore, Magalhães [ 7 ] emphasized that an excessive bureaucracy in the different organizations complicate RTW, and a successful RTW requires a dynamic interdisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the employers reported lacking knowledge on how to support their employees’ RTW and requested more knowledge about how chronic pain might affect work status and the needs and challenges their employees with chronic pain might experience [ 7 ]. For a successful RTW, employers need to effectively collaborate, communicate, and negotiate with their employees, all interactions that require good listening skills [ 8 , 9 ]. In general, barriers to RTW for persons with chronic pain include lack of workplace support, lack of relationships with supervisors and coworkers, and inability to find the right fit between a person’s physical abilities and job tasks [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%